Impact of tablet‐induced electromagnetic interference on abdominal cardiac devices: A study based on simulated patients - Yo Kajiyama; Yusuke Kita; Mayu Iwabuchi; Tomomi Sekine; Keishi Ogura (Journal of Arrhythmia)
Abstract Background Electromagnetic interference (EMI) between tablet computers (tablets) and cardiac implantable electronic devices (CIEDs) in the abdomen of adults remains unclear. Methods We aimed to determine the magnetic flux density (MFD) of tablets, measure the distance at which EMI was triggered, and assess the susceptibility of abdominally implanted CIEDs to EMI. Results We studied 17 tablets and 2 CIED models. The measured MFD of tablets was 638 Gauss. EMI occurred at a 3.2 cm distance. A simulated patient using a tablet experienced EMI episodes for 357.2 s in 10 min. Conclusions Tablets may generate sufficient MFD to induce EMI in abdominally implanted CIEDs.